Konvergensi IFRS: Pengukuran Fair Value Accounting Berdasarkan Kualitatif Informasi - John F. Sonoto (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2013)
This paper aims to describe one issue about IFRS convergence in Indonesia which is the measurement by using the fair value in relation to the information generated based on the qualitative characteristics of information. Globalized development itself requires a good accounting standard required by the capital markets or institutions that have an agency problem caused by the problem of distance between the Principle and agent. The phenomenon is then pushed the International Accounting Standards Boards (IASB) convergence of international accounting standards with IFRS. Financial statements based on historical cost or fail to provide early warning signals about the financial difficulties being experienced by financial institutions. Issue is then a very strong incentive to apply the fair value method instead of historical cost. To meet the information needs of the decision takes effect measurements on the output characteristics of qualitative information. The main key is the fair value measurement of market conditions on or off.Key words: Convergence of IFRS, fair value, historical cost, characteristics of information and market conditions on or off.